Is there a good governance model for the delivery of contemporary transport policy and practice? An examination of Melbourne and Perth - Legacy, C.; Curtis, Carey; Sturup, S. (Elsevier Science Ltd, 2011)
Land use and transport integration (LUTI) is a contemporary planning policy and practice that supports sustainable transport. Attempts to implement LUTI have raised questions about the appropriate organisational structure and the role of governance to deliver this policy. This paper presents the discussions from two public fora held in 2008 in Melbourne and Perth, Australia. Their purpose was to examine the governance arrangements for land use and transport integration. It is concluded that integration of land use and transport agencies does not mean that land use transport integration will be achieved in practice. Rather than simple organisational re-structuring, a focus on networked governance, together with strong regulation, is conducive to inclusive policy development and the implementation of land use and transport integration policies.